PENGELOMPOKAN DATA PMKS MENGGUNAKAN METODE SELF ORGANIZING MAPS - Eko Heru Firdauz; Edy Widodo (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2018)
The purpose of this study is to group the area in Special Region of Yogyakarta (DIY) to find out the characteristics of Social Welfare Issues (PMKS) in DIY 2016 in the grouped area. This is expected to assist the government in making appropriate policies in the formulation of regulations in addressing the problems of social welfare in the DIY region which has an impact on the realization of a prosperous society so as to create a better young generation and improve the quality of life of the community. Cluster analysis used by Data Mining approach with Self Organizing Maps method. The groupings produce 5 Clusters that have different characteristics. Cluster 1 has the capabilities of persons with disabilities, displaced persons and high socio-economic vulnerable women, Cluster 2 has characteristics of persons with disabilities and high susceptibilities, Cluster 3 has a family of psychological and high-scoring social problems, Cluster 4 has characteristics of street children and persons with disabilities high, and Cluster 5 has the characteristics of children dealing with high laws.